2001
DOI: 10.1103/physrevb.65.033403
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field distribution near current contacts of anisotropic materials

Abstract: We have measured the nonuniformity of the electric field near lateral current contacts of the charge-densitywave materials NbSe 3 and o-TaS 3 . In this contact geometry, the electric field increases considerably near a current contact. Fitting our data to an existing model yields values for the conduction anisotropy and a characteristic longitudinal length scale. This length scale is on the same order as the mesoscopic phenomena in charge-density-wave devices. DOI: 10.1103/PhysRevB.65.033403 PACS number͑s͒: 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…We found that nonlocal voltages appeared in the CDW of o-TaS 3 , both below and above the threshold field for CDW sliding. The sign of the observed nonlocal voltage was opposite to that of the spreading resistance [14,15]. In addition to this, the temperature dependence of the nonlocal voltage suggests that the observed nonlocal voltage originates from the CDW.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…We found that nonlocal voltages appeared in the CDW of o-TaS 3 , both below and above the threshold field for CDW sliding. The sign of the observed nonlocal voltage was opposite to that of the spreading resistance [14,15]. In addition to this, the temperature dependence of the nonlocal voltage suggests that the observed nonlocal voltage originates from the CDW.…”
mentioning
confidence: 76%
“…We first compared our observation with a trivial source, known as spreading resistance, which could affect the nonlocal voltage probes [14,15]. When the current is injected from a tiny electrode into a bulk sample, it cannot flow homogeneously until it spreads over a cross section.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Contacts applied to the side of these elongated and often whiskerlike crystals inject current along the low-conductance direction, leading to large contact resistances, large local Ohmic heating, and inhomogeneous current and electric field profiles in the vicinity of the contact. 4 In charge-density-wave ͑CDW͒ conductors such as K 0.3 MoO 3 and o-TaS 3 where the Peierls transition fully gaps the Fermi surface, CDW depinning, and motion, which dramatically increase the longitudinal conductance, can increase the conductance anisotropy to 10 6 or more at helium temperatures. 2 The inhomogeneities in field and current densities associated with side contacts ͓Fig.…”
mentioning
confidence: 99%
“…1͑a͔͒ occur on a longitudinal scale of roughly the crystal thickness times the square root of the conductance anisotropy, or 5 -50 m for typical samples. 4 As a result, side contacts are poorly suited to probing CDW physics at length scales of 10 m and below. They can produce shear and phase slip in the CDW condensate, smearing out the depinning transition and the spectral width of the coherent oscillations that accompany CDW motion, and generating large-amplitude low-frequency electrical noise.…”
mentioning
confidence: 99%